2011
DOI: 10.1142/s0219467811004044
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality Feedback-Based Adaptive Video Definition Improvement for the Space Manipulation Task

Abstract: A novel video definition enhancement technique for space manipulation task is presented in this paper. In contrast to other techniques, we implement our algorithm by considering both the feedback of the image quality (IQ) and the correction of the visual fatigue factor simultaneously. First, when designing the objective IQ evaluation metrics, we employ both the subjective evaluation result of the IQ and the information of the attention region to improve their performances. The canonical correlation analysis te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Full-Reference IQA calculates the error between the test image and the reference image to assess the quality of the test image [3] . On this basis, Li Guoqing et al proposed a multi-level perception decomposition method for full-reference image quality assessment, which firstly used a pre-trained deep network to perform multi-level semantic decomposition on the image to obtain similarity between feature maps of different levels, and finally obtained high-level semantic image quality scores [4] . Zhisen Tang et al extracted various features in the spatial and frequency domains and used random forest algorithm for fusion, which effectively improved the accuracy of the image assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Full-Reference IQA calculates the error between the test image and the reference image to assess the quality of the test image [3] . On this basis, Li Guoqing et al proposed a multi-level perception decomposition method for full-reference image quality assessment, which firstly used a pre-trained deep network to perform multi-level semantic decomposition on the image to obtain similarity between feature maps of different levels, and finally obtained high-level semantic image quality scores [4] . Zhisen Tang et al extracted various features in the spatial and frequency domains and used random forest algorithm for fusion, which effectively improved the accuracy of the image assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Improper lighting will decrease working efficiency [ 5 ], affect task scheduling, or even cause some accidents. For example, in our past research work it can be found that the visual fatigue and the human error rate may be increased when an astronaut participates in some aerospace flight tasks under improper environment lighting [ 6 ]. Figure 1 shows different lighting effects of a display, where: (a) uses one light source; (b) and (c) use two light sources, and (c) suffers from the glare.…”
Section: Introductionmentioning
confidence: 99%